1996
DOI: 10.1113/jphysiol.1996.sp021629
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitutions in the rat Na+, K(+)‐ATPase alpha 2‐subunit alter the cation regulation of pump current expressed in HeLa cells.

Abstract: 1. To study the functional role of negatively charged amino acids (E327 and D925) located in the transmembrane region of the rat a2-isoform of the Na+,K+-ATPase (rat a2*) in ion transport, the effects of mutations on external K+ dependence and internal Na+ dependence of pump currents were assessed by the patch-clamp technique in combination with a system for rapid solution changes. 2. Amino acid residues were replaced by glutamine (E327Q) or leucine (D925L) and were introduced into rat x2* cDNA which encodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Electrophysiological measurements on HeLa cells expressing the ␣2 mutant D925L have demonstrated that the electrogenicity of the pump is retained with this mutation; hence, the 3Na ϩ / 2K ϩ stoichiometry is probably also intact (56). It is noteworthy in this connection that the D923N mutant supported cell viability in our experiments, thus being able to transport Na ϩ and K ϩ and probably to generate a membrane potential.…”
Section: Discussionsupporting
confidence: 55%
“…Electrophysiological measurements on HeLa cells expressing the ␣2 mutant D925L have demonstrated that the electrogenicity of the pump is retained with this mutation; hence, the 3Na ϩ / 2K ϩ stoichiometry is probably also intact (56). It is noteworthy in this connection that the D923N mutant supported cell viability in our experiments, thus being able to transport Na ϩ and K ϩ and probably to generate a membrane potential.…”
Section: Discussionsupporting
confidence: 55%
“…Whole-cell patch clamp studies were performed as described previously (17,(21)(22)(23). Cell capacitance was measured using voltage ramps of 0.8V/s from a holding potential of −50 mV.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…All experiments were performed at room temperature (20°C-22°C). The experimental chamber (0.2 mL) was placed on a microscope stage, and external solution changes were made rapidly using a modified Y-tube technique (21). The Na + /Ca 2+ exchange currents were recorded as previously described.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…The patch pipettes had a resistance of 2 MΩ or less. The experimental chamber (0.2 ml) was placed on a microscope stage, and the external solution changes were made using a modified Y-tube technique (24 3). These external and internal solutions provided isolation of Ca 2+ channel currents (I Ca ) from other membrane currents, such as Na + and K + channel currents, and also from Ca 2+ flux through the Na + /Ca 2+ exchanger (25).…”
Section: Figurementioning
confidence: 99%